Evaluation of Performance Management in Tanjung Unggat Urban Village Employees of Tanjungpinang City - Ibnu Agus Irawan; Mohamad Kurnia Bintan; 3Setia Pramudya; Satriadi (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
The aim of this research is to determine the performance of government officials in implementing effective governance in Tanjung Unggat Village, Tanjungpinang City. This research uses descriptive analysis methods with a qualitative approach. This research was also obtained from the results of interviews, questionnaires and observations. As well as carrying out data analysis in a structured and systematic manner, according to the focus of the problem using performance appraisal theory. The results obtained from this research are that the performance of employees at the Tanjung Unggat Subdistrict Office, in terms of serving the community, has good performance, which can be measured through several indicators such as subdistrict office employees obeying work rules, being able to work together to carry out various activities within an organization including decision making, measuring work results, and interaction with existing regulations. And employees show that the services provided to the community are always carried out seriously, politely, with a sense of responsibility and ethics.